1994
DOI: 10.1177/106907279400200304
|View full text |Cite
|
Sign up to set email alerts
|

Career Assessment With Asian-Americans

Abstract: The current article provides a review of the issues and problems in conducting career assessment with Asian-Americans. Existing information about the assessment of career interests, vocational development, and work values as they pertain to Asian-Americans are reviewed. Special issues in career assessment with Asian-Americans such as occupational segregation in vocational choices, educational attainment, and family influences are also discussed. The article also presents cross-cultural issues to be considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 33 publications
1
62
1
Order By: Relevance
“…Although research has not examined the reason for the lack of match between client and therapist attributions, theorists in multicultural counseling believe the difference between therapist and client attributions of cause of and solution to client problems may be a result of differences in client and counselor worldviews (D. W. Sue & Sue, 2003). Some clients' cultural value systems (e.g., Asian American, Native American), for instance, emphasize fatalism or external causes for client difficulties (LaFromboise, 1988;Leong, 1985;Root, 1998). In contrast, research indicates that therapists often are more inclined to emphasize an internal locus of control for client problems (Donnan & Pipes, 1985;Tracey, 1988), unless there is a clear external precipitant for the client's concern (Hayes & Wall, 1998;Worthington & Atkinson, 1996).…”
mentioning
confidence: 96%
“…Although research has not examined the reason for the lack of match between client and therapist attributions, theorists in multicultural counseling believe the difference between therapist and client attributions of cause of and solution to client problems may be a result of differences in client and counselor worldviews (D. W. Sue & Sue, 2003). Some clients' cultural value systems (e.g., Asian American, Native American), for instance, emphasize fatalism or external causes for client difficulties (LaFromboise, 1988;Leong, 1985;Root, 1998). In contrast, research indicates that therapists often are more inclined to emphasize an internal locus of control for client problems (Donnan & Pipes, 1985;Tracey, 1988), unless there is a clear external precipitant for the client's concern (Hayes & Wall, 1998;Worthington & Atkinson, 1996).…”
mentioning
confidence: 96%
“…For instance many of the present career models and theories have used White, undergraduate college students when being developed and thus have limited applicability and relevance to culturally diverse populations (Fitzgerald & Betz, 1994;Triandis, 1994). In addition, not only are these original career theories and models limited within their scope of application, but they are also based upon limited and faulty assumptions, they confuse and/or inappropriately define terms such as race, ethnicity and minority, and they do not adequately address salient issues for culturally diverse individuals such as those related to socio-political, socio-economic, social psychological, and socio-cultural factors (Leong, 1985(Leong, , 1995Leong & Serafica, 1995). This clearly suggests that there is an absence of a current comprehensive culturally appropriate and effective career model/theory for culturally diverse populations and therefore, this is a cry out to scholars to develop cross-cultural models/theories that are more appropriate, sensitive, relevant and effective to individuals from diverse groups.…”
Section: Theoretical Approaches To Multicultural Career Developmentmentioning
confidence: 97%
“…Although past research has found that immigrants' career choices are strongly infl uenced by parental pressure (Leong and Gim-Chung, 1995), racial prejudice (Lee, 1994), and cultural values (Sodowsky, 1991;Sodowsky, Kwan, and Pannu, 1995), new literature on career aspirations and development among immigrant college students has been relatively scarce. Overall, literature points to generational status, environmental factors, perceived prejudice, acculturation, and parental infl uence as being associated with students' career choices and aspirations.…”
Section: Career Aspirations and Developmentmentioning
confidence: 99%